SISTEM DAN PROSEDUR PEMBERIAN FASILITAS PPN TIDAK DIPUNGUT ATAS JASA KEPELABUHANAN PADA PT. PELABUHAN INDONESIA (PERSERO) CABANG BANJARMASIN - Puan Ramadhana Piutani; Norlena; Ayu Oktaviani (Universitas Lambung Mangkurat, 2022)
The purpose of this study was to determine the system and procedure for providing VAT facilities not collected for port services at PT. Pelabuhan Indonesia (Persero) Banjarmasin Branch. The results showed that the system and procedures for the provision of VAT facilities were not collected by PT. Pelabuhan Indonesia (Persero) Banjarmasin Branch has been running properly and according to Government Regulation Number 50 of 2019 but there are several factors that cause shipping companies / service users to not be able to take advantage of the VAT facility not being collected even though they are categorized as taxpayers who have the right to use the facility.